Performance review of obstetric management in a tertiary hospital: a qualitative study. (7th June 2011) - Greer, O Y O; Goodsell, R; Myriokefalitaki, E; Cameron, M J
Abstract : Introduction: In April 2010, our obstetric department introduced daily departmental meetings for the purposes of performance review and education, with the objective of improving patient safety on the delivery suite. Objective: To identify key areas of good and poor practice in the multidisciplinary intrapartum management of our unit. Setting: Tertiary hospital delivering 5800 neonates/year. Participants: Midwifery and Medical staff. Methods: Semi-structured discussions of 107 cases were undertaken by a multi-disciplinary group and key positive and negative practice points identified. We conducted a qualitative analysis of the data obtained. Results: Analysis of the key outcomes in 107 cases, indicated that the department predominantly managed complex cases successfully, that a multi-disciplinary approach was often sought and that senior involvement occurred frequently. On the other hand, areas highlighted for improvement included documentation, communication between health professionals and a delay in interventions. Conclusions: Discussion of complex obstetric cases in a multi-disciplinary setting provides an arena for frank discussion and identification of positive and negative practice points for the benefit of individual and departmental performance review. This tool would be suitable for use in other obstetric and medical units.